Tree ring δ18O's indication of a shift to a wetter climate since the 1880s in the western Tianshan Mountains of northwestern China. Issue 13 (14th July 2015) - Xu, Guobao; Liu, Xiaohong; Wu, Guoju; Chen, Tuo; Wang, Wenzhi; Zhang, Qiong; Zhang, Youfu; Zeng, Xiaomin; Qin, Dahe; Sun, Weizhen; Zhang, Xuanwen
Abstract Central Asian droughts have drastically and significantly affected agriculture and water resource management in these arid and semiarid areas. Based on tree ring δ18O from native, dominant Schrenk spruce (Picea schrenkiana Fisch. et Mey.), we developed a 300 year (1710–2010) standard precipitation‐evaporation index (SPEI) reconstruction from January to August for China's western Tianshan Mountains. The regression model explained 37.6% of the variation in the SPEI reconstruction during the calibration period from 1950 to 2010. Comparison with previous drought reconstructions confirmed the robustness of our reconstruction. The 20th century has been a relatively wet period during the past 300 years. The SPEI showed quasi 2, 5, and 10 year cycles. Several pluvials and droughts with covariability over large areas were revealed clearly in the reconstruction. The two longest pluvials (lasting for 12 years), separated by 50 years, appeared in the 1900s and the 1960s. The most severe drought occurred from 1739 to 1761 and from 1886 to 1911 was the wettest period since 1710. Compared to previous investigations of hydroclimatic changes in the western Tianshan Mountains, our reconstruction revealed more low‐frequency variability and indicated that climate in the western Tianshan Mountains shifted from dry to wet in 1886. This regime shift was generally consistent with other moisture reconstructions for the northeastern Tibetan Plateau and northern Pakistan and may have resulted from a strengthened westerly circulation. The opposite hydrological trends in the western Tianshan Mountains and southeastern Tibetan Plateau reveal a substantial influence of strengthened westerlies and weakening of the Indian summer monsoon.